NIAT UNTUK MENGAMBIL SERTIFIKASI AKUNTAN DENGAN PENGUJIAN THEORY OF PLANNED BEHAVIOR DAN TEORI MOTIVASI - Dewi, I Gusti Ayu Ratih Permata; Putri, Putu Yudha Asteria; Dewi, Cok Istri Ratna Sari (Universitas Pendidikan Ganesha, 2018)
ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh sikap, norma subektif, kontrol perilaku persepsian, pemahaman, motivasi karir, motivasi ekonomi, dan motivasi prestasi terhadap niat mahasiswa untuk mengambil sertifikasi akuntan profesional ACCA, CA dan CPA. Populasi dalam penelitian ini adalah seluruh mahasiswa S1 program studi Akuntansi Universitas di Bali yang berjumlah 10.624 mahasiswa akuntansi dengan sampel sejumlah 100 mahasiswa. Teknik analisis data yang digunakan pada penelitian ini adalah analisis statistik deskriptif, uji asumsi klasik dan pengujian hipotesis menggunakan analisis regresi berganda. Hasil penelitian ini membuktikan bahwa sikap, norma subektif, pemahaman, motivasi karir, dan motivasi prestasiberpengaruh terhadap niat mahasiswa untuk mengambil sertifikasi akuntan profesional ACCA, CA dan CPA. Sedangkan kontrol perilaku persepsian dan motivasi ekonomi tidak berpengaruh terhadap niat mahasiswa untuk mengambil sertifikasi akuntan profesional ACCA, CA dan CPA.Kata Kunci: Theory of Planned Behavior, Teori Motivasi, Sertifikasi Akuntan ProfesionalABSTRACTThis study aims to analyze the influence of attitudes, subjective norms, perceived behavioral control, understanding, career motivation, economic motivation, and achievement motivation on students' intentions to take the ACCA, CA and CPA professional accountant certification. The population in this study were all undergraduate students of the University of Bali Accounting study program totaling 10,624 accounting students. In this study the authors narrowed the population to the number of students by 10,624 by calculating the sample size which was done using the Slovin technique, so that the sample in this study were 100 students. The data analysis technique used in this research is descriptive statistical analysis, classical assumption test and hypothesis testing using multiple regression analysis. The results of this study prove that attitudes, subjective norms, understanding, career motivation, and achievement motivation affect student intentions to take the ACCA, CA and CPA professional accountant certification. While perceived behavior control and economic motivation do not affect students' intention to take ACCA, CA and CPA professional accountant certification.Keywords: Theory of Planned Behavior, Motivation Theory, Professional Accountant Certification